Screening for anti-titin antibodies in patients with various paraneoplastic neurological syndromes - Berger, Benjamin; Labeit, Siegfried (Journal of neuroimmunology, 2016)
Anti-titin antibodies indicate a paraneoplastic etiology pointing towards a thymoma in myasthenia gravis (MG), but their seroprevalence and potential diagnostic value in patients with other paraneoplastic neurological syndromes (PNS) is unknown. Therefore, we screened the sera of 44 PNS patients with well-characterized onconeural antibodies (anti-Hu, Yo, Ri, CV2/CRMP5, Ma1, Ma2/Ta, or amphiphysin) for anti-titin reactivity. Two patients (4.5%) were positive for anti-titin antibodies: both patients differed regarding the PNS (sensorimotor neuropathy and subacute cerebellar degeneration vs. chorea), well-characterized onconeural antibodies (CV2/CRMP5 vs. Ri), and malignoma (small cell lung cancer vs. breast cancer). However, retrospectively, the patients neither showed any symptoms of MG nor a thymoma on a computed tomographic (CT) scan. The results of this study indicate that anti-titin antibodies without a predictive relevance for MG or thymoma may be present in a small proportion of patients with PNS.
Gesehen am 14.06.2019
Laut Vorlage Volume 295-296